ANALISIS DAMPAK PROGRAM HUTAN KEMASYARAKATAN TERHADAP ASPEK EKONOMI MASYARAKAT (STUDI KASUS DESA TELAGA KECAMATAN PELAIHARI KABUPATEN TANAH LAUT) - Gusti Yudha Grifaldrin; Hafizianoor Hafizianoor; Asysyifa Asysyifa (Universitas Lambung Mangkurat, 2021)
The Community Forestry (HKm), program especially in Tanah Laut Regency, South Kalimantan Province is an example and needs to be a good momentum to show the public that the community is also able to manage forests sustainably. Successful implementation of HKm depends very much on the Forest Farmer Group (KTH) it self. Therefore, the Forest Farmer Group must be able to answer public doubts about the community's ability to manage forests sustainably. Other forest farmer groups are also expected to be encouraged and competed to plan, and propose to obtain permits for the management of forest areas (Fauzi, 2016). This research is to describe the business development of the HKm program and its development in Telaga Village. Analyzing community income from the HKm program and efforts beyond HKm in Telaga Village. Community Revenue Program from HKm Business in Telaga Village. . Results of research The types of businesses that became the HKM commodity of Telaga village were oyster mushroom cultivation and honey bee culture. The income of KTH Subur Makmur members outside of HKm as the principal income is greater than the operating income of HKm. The average monthly income from the HKm business is Rp. 600,000 and non-HKm average income of Rp. 3,735,000. The contribution of HKm business to KTH Subur Makmur members is 15.96%. The revenue contribution came from the sale of honey and oyster mushrooms. Non-HKm revenue contribution of 84.04%Keywords: Commodities, Contributions, Community Forestry (HKm), Telaga Village